Relativistic dynamics of [Formula Presented] systems - Suisso, E. F.; de Melo, J.P.B.C. [UNESP]; Frederico, T. (American Physical Society (APS), 2002)
The bound state of constituent quarks forming a (Formula presented) composite baryon is investigated in a QCD-inspired effective light-front model. The light-front Faddeev equations are derived and solved numerically. The masses of the spin 1/2 low-lying states of the nucleon, (Formula presented) (Formula presented) and (Formula presented) are found and compared to the experimental data. The data are qualitatively described with a flavor independent effective interaction. © 2002 The American Physical Society.